2014
DOI: 10.1177/016146811411600103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Intended and Unintended Consequences of High-Stakes Teacher Evaluation on Schools, Teachers, and Students

Abstract: Background/Context The stakes are getting higher for teachers daily as more and more states adopt hiring, firing, and tenure-granting policies based on teacher evaluations. Even more concerning is the limited discussion about whether or not high-stakes teacher evaluation can meet the intended outcome of improved student achievement, and at what cost. These high-stakes decisions are based on the rationale that firing ineffective teachers (as primarily measured by observation data and value-added scores) will im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…While not central to our guiding research questions on the relationship of evaluators to important changes in teacher motivation and practice, one notable and consistent finding from our study is the negative relationship between a principal’s use of extrinsic motivational tools after evaluation, such as rewards and consequences, and teacher outcomes (e.g., practice/motivation). Scholars have warned about the negative ramifications of high-stakes evaluation (Ford et al, 2018; Guenther, 2021; Holloway et al, 2017; Lavigne, 2014; W. C. Smith & Holloway, 2020) where teacher evaluation outcomes are tied to extrinsic rewards such as promotion, salary increase, etc., particularly on factors such as teacher affective states, motivation, retention, and school culture and climate.…”
Section: Discussionmentioning
confidence: 99%
“…While not central to our guiding research questions on the relationship of evaluators to important changes in teacher motivation and practice, one notable and consistent finding from our study is the negative relationship between a principal’s use of extrinsic motivational tools after evaluation, such as rewards and consequences, and teacher outcomes (e.g., practice/motivation). Scholars have warned about the negative ramifications of high-stakes evaluation (Ford et al, 2018; Guenther, 2021; Holloway et al, 2017; Lavigne, 2014; W. C. Smith & Holloway, 2020) where teacher evaluation outcomes are tied to extrinsic rewards such as promotion, salary increase, etc., particularly on factors such as teacher affective states, motivation, retention, and school culture and climate.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of eight articles provided evidence that educational policies designed to evaluate teachers based on student test scores did not accomplish their intended consequences (Berliner, 2014;Hill et al, 2011;Kupermintz, 2003;Lavigne, 2014;Martineau, 2006;Moore Johnson, 2015;Polikoff, 2015;Rothstein, 2010). Kupermintz (2003) presented evidence supporting several alternative explanations of student gains, warning that "policy makers and administrators who wish to use [VAMs] must consider these alternative explanations when contemplating the likely consequences, intended and unintended, of any policy move" (p. 289).…”
Section: Validity Evidence Based On Related Consequencesmentioning
confidence: 99%
“…Similarly, Hill et al (2011) stated that their case study findings "lead [them] to conclude that value-added scores, at least in [the] district [of study] and using these not-uncommon models, [were] not sufficient to identify problematic and excellent teachers accurately" (p. 825). Finally, an article written by Lavigne (2014) was entirely devoted to validity evidence based on related consequences, in which she concluded that high-stakes accountability systems based on student test scores failed to achieve their intended consequences, at a cost of several negative unintended consequences instead.…”
Section: Validity Evidence Based On Related Consequencesmentioning
confidence: 99%
“…Advocates argue that edTPA's scores should serve to assess program quality and achieve accreditation from the Council for Accreditation of Educator Preparation and/or provide a framework for program development and design (SCALE, n.d.). There is strong support in the literature for the use of the edTPA to make licensure and program decisions (Bartell et al, 2018;Conley & Garner, 2015;Lavigne, 2014;Lys et al, 2014;Peck et al, 2014;SCALE, 2015). There are also discussions related to issues of validity and the edTPA (Duckor et al, 2014;Goldhaber et al, 2016;Haertel & Herman, 2005;Henry et al, 2013;Sato, 2014); some argue for its predictive value (Goldhaber et al, 2016;Henry et al, 2013;Sato, 2014).…”
Section: Relevant Literaturementioning
confidence: 99%